Observations of high concentrations of I2 and IO in coastal air supporting iodine-oxide driven coastal new particle formation - Huang, Ru-Jin; Seitz, Katja; Neary, T.; O'Dowd, C. D.; Platt, Ulrich; Hoffmann, T. (Geophysical research letters, 2010)
Theoretical studies have predicted that concentrations of gaseous I2 and IO of the order of 80-100 ppt and 40-50 ppt, respectively, are required in coastal air to account for photochemically-driven coastal new-particle formation events to occur. However, measurements reported to date (i.e., ∼20 ppt I2, ≤ 10 ppt IO) have not supported the required model predictions. Here, we present measurements of high concentrations of I2 and IO in N.E. Atlantic marine air on the west coast of Ireland. The maximum mixing ratios of daytime I2 and IO over the seaweed beds during low tide were 302 ppt and 35 ppt, respectively. The I2 distribution was rather inhomogeneous, even at the inter-tidal zone, but closely related to the macroalgae biomass abundance. New particle formation bursts were frequently observed during daytime hours with the concentrations up to 4.5 × 105 particles cm−3 during low-tide conditions, and the concentrations of ultra-fine particles were positively correlated with the IO concentrations. Considering the constraints set out in theoretical studies for new particle formation via condensation of condensable iodine oxide vapours, the results reported here clearly demonstrate that the molecular iodine and iodine monoxide concentrations in coastal air are sufficient to meet the theoretical precursor concentrations required to drive intensive coastal new-particle formation from higher order condensable iodine oxides.